An unobserved component analysis of Malaysia's house prices. Issue 3 (1st February 2018) - Mohd Daud, Siti Nurazira; Marzuki, Ainulashikin
Abstract : Purpose: This paper aims to investigate Malaysia's house prices behaviour by decomposing trend, cycle and stochastic component. Design/methodology/approach: The authors perform an unobserved component model of a structural time series and Markov switching model that covers the period 1999Q1 to 2015Q4. Findings: The results reveal that the variation in house price in Malaysia is best explained by its trend level, with a small role played by the cycle component; this implies the potential for gaining returns on investments in property by investors and households. The results also show that Malaysia's HPI cycle is between 8 and 17 years which, in relative terms, is twice the length of the growth cycle and the business cycle in the economy. Meanwhile, the overall movement of HPI is forecast to have a marginal price increase up to 2028Q2. Originality/value: As house prices remained elevated during the year, the house price dynamic is pivotal for understanding the source of changes in house price. With major findings centred on the relationship between house prices and macroeconomic as well as policy variables, little attention has been paid to composing the trend, cycle and seasonal pattern from the house price index, thus understanding the behaviour of house prices' unobserved components.